A Brief Review on the Present Status, Problems And Prospects of Maize Production in Bangladesh (Research in Agriculture Livestock and Fisheries, 2022)
Maize is one of the promising crops for foods, green forage and industrial uses. There is lot of research about maize regarding various aspects in Bangladesh. However, no published review report on the present status, problems and prospects of maize production in Bangladesh has been found. In this review, we provided intensive information to increase maize production and profitability in Bangladesh from all the available resources i.e., journal article, book, proceeding and electronic sources. This paper showed that maize cultivation was more profitable in Bangladesh and indicated some problems with maize cultivation as well as suggested some recommendations to improve maize production. Understanding all the facts about this paper will boost to maize production in Bangladesh and assist to researchers to choose advance topics about the improvement of maize cultivation.Vol. 9, No. 2, August 2022: 89-96